DILEMA DIGITALISASI TELEVISI DI LEVEL LOKAL (Studi Eksplorasi Problematika Persiapan Regulator dan Pelaku Penyiaran Lokal Daerah Istimewa Yogyakarta Dalam Peralihan Ke Sistem Siaran Televisi Digital) - , TANTIDA ISA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Digital television broadcasting system is now become a trending topic and said by television broadcasting around the world since the conference was held by International Telecommunication Union (ITU) in Geneva, 2006. Indonesian government tried to adopt the digital television broadcasting system by using the issue of ministerial regulation, Indonesian ministry of communications and information technology No. 22/PER/M.KOMINFO/11/2011. However, this policy has pros and contras between the government, the regulator, and broadcasters. Now, the government has new issue of ministerial regulation Indonesian ministry of communications and information technology Kepmen Kominfo No.95 tahun 2012 which decide about Daerah Istimewa Yogyakarta and six others cities which chosen to be a zone of simulcast services but the problems about the regulation still on the way. Because of getting variety of demands and rejections from various circle, so the supreme court decided to cancel this policy in April the 3rd 2013. To face the problem about the application digital television broadcasting system in Indonesia, it is important to learn about the preparation and readiness of local broadcasters and regulators in dealing with the transition to digital television broadcasting system. This study of exploration was doing the exploration about preparation and readiness of local broadcasters and regulators, which one as a simulcast zone. This exploration has been able mapping the preparation of digital television broadcasting in DIY by macros problematic. It is used as reference to analyze the weaknesses of digital television broadcasting in Indonesia. Analyze use critical perspective, can getting many problems about applications in local digital television broadcasting system. This study can be expected to give contribute and reference for the government to apply digital television broadcasting system and the next research about digital television broadcasting system.